Knowledge, attitude and practice of pesticide use and serum cholinesterase levels among rice farmers in Nakhon Nayok Province, Thailand - Sapsatree Santaweesuk; Paisit Boonyakawee; Wattasit Siriwong (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - The study purposes were to investigate the knowledge, attitude and practice of pesticide use and to determine the levels of serum cholinesterase among rice farmers in Nakhon Nayok province, Thailand. Design/methodology/approach - A cross-sectional study was carried out in communities in Nakhon Nayok Province, Thailand. Multistage random sampling was employed, selecting one person per each rice farmer household. Data was collected from 188 rice farmers using a structured face-to-face interview questionnaire. A reactive-paper finger-blood test was used to determine SChE levels. Chi-square test was used to determine the relationship between the practice of pesticide use and SChE levels. Findings - The results indicated that the rice farmers had a fairly good knowledge and a neutral attitude toward the practice of pesticide use. Most of the respondents had a fairly proper practice of pesticide use. However, serum cholinesterase levels of the farmers were unsafe and risky. It signified that 68.1% of the farmers had a health risk from using pesticides. The prevalence of abnormal SChE levels among rice farmers with improper use was significantly higher than that among rice farmers who had a proper use. Research limitations/implications - The result provided a guideline for operational planning and control and prevention of health effects from pesticides use in farmers or other agriculturists who use pesticides in cultivation. Practical implications - Concerned local agencies especially health-related agencies are able to conduct a training to educate and build safety awareness including monitoring continuously the safety behaviors toward pesticides use. It can be implemented by establishing leaders from health promoting hospitals led by village health volunteers, community leaders and participation from farmers to collaboratively monitor proper use of pesticides beginning with health surveillance in the abnormal SChE group to be screened for pesticide exposure every six months or one year. Social implications - Farmers gained knowledge and understanding of pesticides use and used it properly, which resulted in a reduction of pesticide residues in body as well as in the environment. In addition, the government policy should legislate measures for related agencies to promote proper use of pesticides. For instance, Department of Agriculture, Minister of Agriculture and Cooperatives should regularly supervise, monitor and inspect the production and distribution of pesticides in local shops and also systematically encourage agriculturists to adopt using pesticides that are less harmful. Originality/value - Having knowledge, understanding and proper practices toward pesticides use, farmers can reduce health effects of pesticides use in themselves and family members.